Echocardiographic Evaluation and Clinical Implications of Aortic Stiffness and Coronary Flow Reserve and their Relation - Nemes, Attila (Clin Cardiol, 2007)
The normal human aorta is not a stiff tube but is characterized by elastic properties with a buffering Windkessel function. Aortic stiffening may cause an increase in aortic pulse pressure, left ventricular load, and ultimately left ventricular hypertrophy. This, together with the decreased diastolic transmyocardial pressure gradient interacts with coronary flow and flow reserve. In recent studies, significant correlations between coronary flow reserve and aortic stiffness have been demonstrated in different patient populations. The aim of the present review is to describe the current echocardiographic modalities to measure aortic stiffness and coronary flow reserve and to overview our knowledge about the relationship between aortic stiffness and coronary flow reserve. Copyright © 2007 Wiley Periodicals, Inc.